The Relationship between Executive Functions and Dance Classes in Preschool Age Children - Elena Chichinina; Daria Bukhalenkova; Alla Tvardovskaya; Yury Semyonov; Margarita Gavrilova; Olga Almazova (Education Sciences, 2022)
The development of executive functions is of the utmost importance for academic success at school and the social adaptation of children. Dance class attendance is one of the factors promoting the development of these functions in children. This study was aimed to explore the relationship between extra dance class attendance and executive functions in preschool age children. The executive function level was assessed using NEPSY-II subtests “Sentences Repetition”, “Memory for Designs”, “Inhibition”, “Statue”, and “Dimensional Change Card Sort”. The data on extra dance classes were collected by means of a questionnaire for parents. In the study, 86 typically developing 5–6-year-old children participated. No statistically significant differences in executive functions’ levels were discovered in children taking only extra dance classes for at least 6 months and children taking no extra classes. The obtained data plays an important role for the design of further investigations of the topic.